2020
DOI: 10.1101/2020.01.31.928440
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Osh6 requires Ist2 for localization to the ER-PM contacts and efficient phosphatidylserine transport

Abstract: Osh6 and Osh7 are lipid transfer proteins (LTPs) that transport phosphatidylserine (PS) from the endoplasmic reticulum (ER) to the plasma membrane (PM). High PS level at the PM is key for many cellular functions. Intriguingly, Osh6/7 localize to ER-PM contact sites, although they lack membrane-targeting motifs, in contrast to multidomain LTPs that both bridge membranes and convey lipids. We show that Osh6 localization to contact sites depends on its interaction with the cytosolic tail of the ER-PM tether Ist2,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…In contrast, there was a significant increase in the localisation of the PI4P FLARE (GFP-P4C) at the PM in scs2/22 Δ ist2 Δ cells, as compared to wild type control cells ( Figures 2B and C ). Previous studies have shown that Scs2/22 and Ist2 recruit the PI4P exchange proteins Osh2, Osh3, Osh6, and Osh7 to ER-PM contacts (Loewen and Levine, 2005; D’Ambrosio et al, 2020) and loss of Scs2/22 and Ist2 results in increased PI4P levels (Manford et al, 2012). As Tcb-mediated ER-PM contacts are induced in cells lacking Scs2/22 and Ist2 ( scs2/22 Δ ist2 Δ), we next monitored distribution of the PI4P and PI(4,5)P 2 FLAREs in scs2/22 Δ ist2 Δ cells that also lacked the Tcb proteins (Δtether).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, there was a significant increase in the localisation of the PI4P FLARE (GFP-P4C) at the PM in scs2/22 Δ ist2 Δ cells, as compared to wild type control cells ( Figures 2B and C ). Previous studies have shown that Scs2/22 and Ist2 recruit the PI4P exchange proteins Osh2, Osh3, Osh6, and Osh7 to ER-PM contacts (Loewen and Levine, 2005; D’Ambrosio et al, 2020) and loss of Scs2/22 and Ist2 results in increased PI4P levels (Manford et al, 2012). As Tcb-mediated ER-PM contacts are induced in cells lacking Scs2/22 and Ist2 ( scs2/22 Δ ist2 Δ), we next monitored distribution of the PI4P and PI(4,5)P 2 FLAREs in scs2/22 Δ ist2 Δ cells that also lacked the Tcb proteins (Δtether).…”
Section: Resultsmentioning
confidence: 99%
“…Under normal growth conditions (left panels), non-vesicular phosphatidylserine (PS, magenta) transport from the ER to the PM is carried out by Osh6 and Osh7 that are recruited to ER-PM contacts by Ist2 (D’Ambrosio et al, 2020). Osh6 and Osh7 move PS from the ER to PM in exchange for PI4P (yellow) at the PM (top left, Wild type cells).…”
Section: Discussionmentioning
confidence: 99%
“…Although Osh6 and Osh7 contain only an ORD domain, they show a well-defined localization at the ER-PM contacts ( Schulz et al, 2009 ; Maeda et al, 2013 ). We have recently demonstrated that the localization of Osh6 to this MCS is mediated by another protein, Ist2 ( D’Ambrosio et al, 2020 ). Importantly, the interaction between Osh6/7 and Ist2 is required for their PS transfer activity in cells ( D’Ambrosio et al, 2020 ) and for the subsequent processing of PS into PE by Psd2 ( Wong et al, 2021 ) ( Figure 2C ).…”
Section: Organelle Targeting Of Ps Transfer Proteinsmentioning
confidence: 99%
“…We have recently demonstrated that the localization of Osh6 to this MCS is mediated by another protein, Ist2 ( D’Ambrosio et al, 2020 ). Importantly, the interaction between Osh6/7 and Ist2 is required for their PS transfer activity in cells ( D’Ambrosio et al, 2020 ) and for the subsequent processing of PS into PE by Psd2 ( Wong et al, 2021 ) ( Figure 2C ). Unlike the adaptors mentioned earlier, Ist2 is itself a tethering protein between the ER and the PM.…”
Section: Organelle Targeting Of Ps Transfer Proteinsmentioning
confidence: 99%
“…In yeast cells, ER-PM MCSs are also major determinants of phospholipid regulation. Akin to ORP5/8 in mammalian cells, yeast Osh6p/7p is recruited to ER-PM MCSs by the tether Ist2p, where Osh6p transfers PS in the ER to the PM for the reciprocal exchange of PM PI4P back to the ER ( Maeda et al, 2013 ; Moser von Filseck et al, 2015a ; D’Ambrosio et al, 2020 ). PE transported to the PM is converted to PC by the ER-localized Opi3p ( Kodaki and Yamashita, 1987 ; McGraw and Henry, 1989 ).…”
Section: The Cellular Coordination Of Phospholipid Metabolism and Tramentioning
confidence: 99%